AI vs. human mind: efficiency in the management of construction industry - Ang Soon Ern, Peniel; Jong, Oi Ka; Safea’ai, Muhammad Aqerul; Mohd Saip, Muhammad Amirul Rasyid; Mohamed Salehin, Nur Ili Izyan (Penerbit UTHM, 2022)
The digitalisation of construction industry is driving to embrace smart construction with emerging technologies for its productiveness. Artificial Intelligent (AI) is one of the cutting-edge technologies that demonstrates efficiency and effectiveness in construction project lifecycle. For instance, prevent cost overrun, create generative design with Building Information Modelling (BIM), conduct logistics management in site, and perform periodic facility management. Despite the significant implications of AI in construction value chain, there are disagreements among the community on the effectiveness of AI implementation in construction industry. Hence, this study compares the efficiency of both AI and human mind in the management of construction industry. The result presented that AI play an important role to assist human in resolving high volume of data effectively, store massive data securely at a place and unlimited usage to complete repetitive work. This study breaks the perception of public where AI implementation could replace human mind or it is a cumbersome process to adopt. The characteristic of AI should be utilised to improve the efficiency and productivity of construction management.